1988
DOI: 10.1063/1.340500
|View full text |Cite
|
Sign up to set email alerts
|

Boron diffusion in silicon at high concentrations

Abstract: Computational methodology for analysis of the Soret effect in crystals: Application to hydrogen in palladium J. Appl. Phys. 112, 083516 (2012) Spectroscopic analysis of Al and N diffusion in HfO2 J. Appl. Phys. 112, 064118 (2012) Copper centers in copper-diffused n-type silicon measured by photoluminescence and deep-level transient spectroscopy Appl. Phys. Lett. 101, 042113 (2012) Bonding and diffusion of nitrogen in the InSbN alloys fabricated by two-step ion implantation Appl. Phys. Lett. 101, 021905 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…It shows a prominent kink in highconcentration diffusion profiles (Duffy et al, 1968;Tsai, 1969) and was also found to accelerate the diffusion of other dopants separated spatially (Miller, 1960;Yeh, 1962). Similar effects were found for boron, although less pronounced (OrrArienzo et al, 1988).…”
Section: System Behaviorsupporting
confidence: 85%
“…It shows a prominent kink in highconcentration diffusion profiles (Duffy et al, 1968;Tsai, 1969) and was also found to accelerate the diffusion of other dopants separated spatially (Miller, 1960;Yeh, 1962). Similar effects were found for boron, although less pronounced (OrrArienzo et al, 1988).…”
Section: System Behaviorsupporting
confidence: 85%
“…For this specific case the (G-R) terms linked to the interstitial-related clusters evolution vanish, and such simulations can thus be used to fit the basic parameters describing the dopant interactions with the free point defects. As shown on Figure 1, the agreement between the experimental profiles [4] and the simulated ones, with parameters corresponding to a I contribution to the total B diffusion of the order of 85 %, is remarkably good.…”
Section: Silvaco I N T E R N a T I O N A Lsupporting
confidence: 54%
“…Comparison between calculated and experimental boron predeposition profiles. Experimental data are from ref [4]. …”
mentioning
confidence: 99%
“…Boron and phosphorus diffusions were performed in a tube furnace employing liquid sources: BBr 3 liquid source for boron and POCl 3 liquid source for phosphorous. To achieve comparable junction characteristics, boron diffusion in Si requires much higher diffusion temperatures than phosphorus diffusion in Si 11, 12. As a means to assure optimum boron and phosphorus diffusion conditions minimizing their impact on the post‐diffusion wafer lifetime, we measured the effective minority carrier lifetime as a function of the excess minority carrier density Δ n (at 10 15 cm −3 injection level) using the quasi‐steady‐state photoconductance (QSS‐PC) technique 13…”
Section: Methodsmentioning
confidence: 99%